2017
DOI: 10.1155/2017/6817196
|View full text |Cite
|
Sign up to set email alerts
|

Heating Has No Effect on the Net Protein Utilisation from Egg Whites in Rats

Abstract: Egg whites (EW) are a good source of protein; however, they are typically heated prior to consumption. Therefore, we investigated the effects of different heating conditions on the protein utilisation rate of EW. Male Sprague-Dawley rats (n = 36, 198 ± 1 g) were divided into six groups and fed American Institute of Nutrition-76 chow containing unheated EW, soft-boiled EW, boiled EW, milk whey protein, soybean protein, or no protein over a 10-day period using pair-feeding. Urine and faeces were sampled daily be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Egg white proteins mainly including ovalbumin, ovotransferrin, ovomucoid and lysozyme, are widely available and show a well-balanced profile of amino acids with high bioavailability (Abeyrathne, Lee, & Ahn, 2013;Matsuoka, Takahashi, Kimura, Masuda, & Kunou, 2017). Besides their nutritional characteristics, the denaturation and aggregation behaviour of these proteins is of particular relevance toward manufacture of hydro-or emulsion gel structures which can act as nutrients or drug delivery systems (Drakos & Kiosseoglou, 2006;Opazo-Navarrete, Altenburg, Boom, & Janssen, 2018;Tomczyńska-Mleko et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Egg white proteins mainly including ovalbumin, ovotransferrin, ovomucoid and lysozyme, are widely available and show a well-balanced profile of amino acids with high bioavailability (Abeyrathne, Lee, & Ahn, 2013;Matsuoka, Takahashi, Kimura, Masuda, & Kunou, 2017). Besides their nutritional characteristics, the denaturation and aggregation behaviour of these proteins is of particular relevance toward manufacture of hydro-or emulsion gel structures which can act as nutrients or drug delivery systems (Drakos & Kiosseoglou, 2006;Opazo-Navarrete, Altenburg, Boom, & Janssen, 2018;Tomczyńska-Mleko et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The digestibility and net protein utility values of ESM-P and ESM-H were lower than representative values for white proteins [10]. This may be because of the low content of the essential amino acids phenylalanine + threonine and leucine (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ESM-P include collagen type I, V, and X, and protein derived from egg white [8, 9]. The net protein utility values of proteins in white have been reported to be higher than those of other protein sources [10].…”
Section: Introductionmentioning
confidence: 99%
“…Egg white protein (EWP) has an amino acid score of 100 [1, 2], and has been reported to retain a high level of bioavailability even when not heated, or after half-boiling or heating cooking processes [3]. We have previously reported, in an animal experiment, that the consumption of egg white protein increases the body’s protein mass while decreasing the body fat and visceral fat [4].…”
Section: Introductionmentioning
confidence: 99%